(untitled) (Journal of Dhaka Medical College, 2021)
Secretory carcinoma is an extremely rare subtype of low grade invasive breast carcinoma and occurs infrequently in adults showing belligerent clinical course than in children. Surprisingly, it is the only epithelial carcinoma of breast representing characteristic balanced translocation.This paper reports a case of secretory breast carcinoma in an elderly post-menopausal woman in Bangladesh which is diagnosed by core needle biopsy. The majority of the case reports claimed this tumor to be a triple negative breast carcinoma, whereas our case report reveals a slightly different status in immunohistochemical context. A 78-years old, post-menopausal female presented with the chief complaints of painless, slowly enlarging lump in her left breast over nine months. Breast examination revealed a 2x1.5cm, well-delineated, firm, non-tender and mobile mass in the lower-outer quadrant of the left breast. Microscopically, the tumor was composed of cells containing PAS positive, diastase resistant and mucicarmine positive intra and extra-cellular secretory material and Alcian blue positive secretion was found extracellularly. The tumor cells showed strongly positive immunohistochemical reactivity for cytokeratin, EMA, E-cadherin and vimentin and focal positive reaction for S-100 protein and estrogen receptor but negative for both progesterone receptor and human epidermal growth factor receptor. Ki-67 proliferative index was about 4%. Hence, the diagnosis of secretory breast carcinoma (SBC) was made. The patient underwent modified radical mastectomy with axillary clearance without any axillary lymphnode involvement in an external center. The patient has not received any radio or chemotherapy. The patient was under continuous follow-up for 3-months.Unfortunately, owing to the nation-wide lockdown for dreadful COVID-19 pandemic, the patient couldn’t arrive at the hospital for further follow-up evaluation. Immunohistochemical (IHC) analysis has been proven to be an alternative potential method as gene analysis. Immunoprofiling of secretory breast carcinomas may play the pivotal role for selecting therapeutic strategies and predicting prognostic outcome of the disease process. Comprehending the immunohistochemical expression would make scope for applying targeted therapy in SBC patients in future. J Dhaka Medical College, Vol. 28, No.2, October, 2019, Page 216-223